Functional outcome of the distal femur fractures using plate osteosynthesis - Shingati Muhammed Hashim,; Sahuji, Sachin (International Journal of Research in Medical Sciences, 2023)
Background: Distal femoral fractures are a catastrophic event with bimodal distributions. Despite the advances in techniques and the improvements in surgical implants, treatment of distal femoral fractures still remains a challenge in many situations. The purpose of this study is to evaluate the rate of union, functional outcome and complications of these fractures treated by open reduction and internal fixation via plate osteosynthesis. Objectives were-1. Whether fractures reduction and fixation with plate will give acceptable results in the distal femur fractures treated in our setup. 2. To study the clinical outcome associated with this treatment modality and 3. What are the potential associated complications Methods: This is a prospective, randomized observational study of 17 patients, with distal femur fractures (Muller classification type 33 A, C) who were treated with DFLCP at department of orthopaedics, Raja Rajeswari medical college hospital, Bangalore from January 2021 to July 2022. The study sample was 17 patients and all these patients were included with predefined inclusion and exclusion criteria in this study. Minimum of 2 months and a maximum of 12 months follow up was done. The functional and radiographic results were recorded according to Neer’s criteria. Results: In this study, most of the patients in this study were patients in the age group 61-75 years. The 53% of the cases were Muller type A and 47% were type C. The shortest follow up period was 2 months and longest period was 12 months, average union time was 18 weeks. Most common complications are knee stiffness, infection and shortening. In this study, there were two cases with excellent results, nine cases with good results, four cases with fair results and no cases went for failure. Conclusions: We conclude that using locking plates is a safe and reliable method although careful preoperative planning and case selection and taking up cases for surgery as soon as possible are important factors which determine the final outcome.